Quadratic numerical treatment for singular integral equations with logarithmic kernel - Nadir, Mostefa; Gagui, Bachir (Université de M'sila, 2018)
The goal of this paper is to present a direct method for an approximative solution of a weakly singular integral equations (WSIE) with logarithmic kernel on a piecewise smooth integration path using a modified quadratic spline approximation, we also show that this approximation gives an efficient approach to the analytical solution of WSIE.
Keywords: weakly singular integral; quadratic interpolation; holder space and holder condition.